C-peptide Targets and Patient-centered Outcomes of Relevance to Cellular Transplantation for Diabetes. Issue 3 (21st February 2023) - Verhoeff, Kevin; Marfil-Garza, Braulio A.; Dajani, Khaled; Bigam, David L.; Anderson, Blaire; Kin, Tatsuya; Lam, Anna; O'Gorman, Doug; Senior, Peter A.; Shapiro, A. M. James
Abstract : Background: C-peptide levels are a key measure of beta-cell mass following islet transplantation, but threshold values required to achieve clinically relevant patient-centered outcomes are not yet established. Methods: We conducted a cross-sectional retrospective cohort study evaluating patients undergoing islet transplantation at a single center from 1999 to 2018. Cohorts included patients achieving insulin independence without hypoglycemia, those with insulin dependence without hypoglycemia, and those with recurrent symptomatic hypoglycemia. Primary outcome was fasting C-peptide levels at 6 to 12 mo postfirst transplant; secondary outcomes included stimulated C-peptide levels and BETA-2 scores. Fasting and stimulated C-peptide and BETA-2 cutoff values for determination of hypoglycemic freedom and insulin independence were evaluated using receiver operating characteristic curves. Results: We analyzed 192 patients, with 122 (63.5%) being insulin independent without hypoglycemia, 61 (31.8%) being insulin dependent without hypoglycemia, and 9 (4.7%) experiencing recurrent symptomatic hypoglycemia. Patients with insulin independence had a median (interquartile range) fasting C-peptide level of 0.66 nmol/L (0.34 nmol/L), compared with 0.49 nmol/L (0.25 nmol/L) for those being insulin dependent without hypoglycemia and 0.07 nmol/L (0.05 nmol/L) for patients experiencing hypoglycemia ( P < 0.001). Optimal fasting C-peptide cutoffs for insulin independence and hypoglycemia were ≥0.50 nmol/L and ≥0.12 nmol/L, respectively. Cutoffs for insulin independence and freedom of hypoglycemia using stimulated C-peptide were ≥1.2 nmol/L and ≥0.68 nmol/L, respectively, whereas optimal cutoff BETA-2 scores were ≥16.4 and ≥5.2. Conclusions: We define C-peptide levels and BETA-2 scores associated with patient-centered outcomes. Characterizing these values will enable evaluation of ongoing clinical trials with islet or stem cell therapies. Abstract :